The - International Institute for Strategic Studies (Oxford University Press, 2000)
The Military Balance 2000/2001 is an indispensable reference work, providing data on the military strength, organization, equipment, and defence expenditure of the world's armed forces in some 170 countries. It also contains short analytical articles on topical military and strategic issues